Analysis of correlation between regional implant density and the correction rate in treatment of Lenke 1A and 1B adolescent idiopathic scoliosis with pedicle screws. Issue 2 (January 2018) - Li, Yanming; Yang, Changwei; Zhu, Xiaodong; Li, Ming
Abstract : Abstract: A retrospective study. The optimal implant density in patients with Lenke type 1 adolescent idiopathic scoliosis (AIS) is undefined, and there is no study reporting the correlation between the partitional implant density and the correction outcome. To determine whether the implant density in structural and nonstructural regions would affect the coronal correction outcome of Lenke 1A and 1B AIS. Preoperative general data and postoperative follow-up data of Lenke 1A and 1B AIS patients who received posterior fusion with the pedicle screw system were analyzed. Correlations between the implant density in structural and nonstructural regions and the correction rate of coronal Cobb angle, as well as between the correction rate and loss of the coronal correction angle during a 2-year follow-up period were analyzed. According to the implant density, the patients were classified into 2 groups: structural region group (including A1 and A2), and nonstructural region group (including B1 and B2). Differences in related parameters between the 2 groups were compared statistically. Except for the mean implant density, there was no statistical difference in the other parameters between group A1 and A2. In group B1 and B2, the correction rate of the main thoracic (MT) curve was 63.0% and 71.6% ( P  = .022), and the loss of the correction angle was 2.1° and 4.2°, respectively ( P  < .01), showing a statistical difference in the correction rate and postoperative angle loss of the MT curve between group B1 and B2. The correction rate of the MT curve at the coronal plane and postoperative loss of the correction angle were not related to the implant density in structural regions but may be related to the implant density in nonstructural regions in the treatment of Lenke type 1A and 1B AIS with pedicle screw instrumentation.